FACTORS INFLUENCING CYBER-AGGRESSION: A SYSTEMATIC REVIEW - Moesarofah, Moesarofah (LP2M IAI Al-Khairat Pamekasan, 2025)
This systematic literature review aims to synthesize factors contributing to cyber aggression, drawn from various empirical studies. This review examines individual, social, and situational factors that shape the tendency of cyber aggression, as well as the interaction between factors. Referring to Grigg's theory, the dynamics of cyber aggression are influenced by various factors, ranging from the motivation of the perpetrator to the conditions of the social environment. Several relevant theories to explain such as Social Learning Theory, Cognitive Theory and Frustration-Aggression Theory. The research design uses a systematic literature review, from 2010-2024. Search through electronic databases: Frontiers, Elsevier, Springer, Routledge, and Google Scholar. Search keywords: